MEMBANGUN KETAHANAN FINANSIAL KELUARGA MUSLIM: PENGARUH RELIGIUSITAS TERHADAP PERILAKU PENGELOLAAN KEUANGAN - Hayatul Khairul Rahmat; A Said Hasan Basri; Mursalim Mursalim; Yedi Sispurwanto (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2026)
Muslim families in Indonesia face increasingly complex financial pressures, ranging from rising living costs to the high prevalence of problematic online lending, making the ability to manage household finances soundly an urgent need. Religiosity is believed to be an important driver of responsible financial behavior, yet the mechanism and strength of its influence on family financial management behavior remain mixed in the literature. This study aims to analyze the influence of religiosity on Muslim family financial management behavior, both directly and through the mediation of Islamic financial literacy. This study employed a quantitative causal-explanatory approach with a cross-sectional survey design involving 320 heads of households/spouses responsible for managing household finances in the urban areas of Greater Jakarta, Greater Bandung, and Greater Surabaya, selected through purposive sampling. Data were collected through a five-point Likert-scale questionnaire adapting the Centrality of Religiosity Scale, a basic Islamic financial literacy instrument, and a financial management behavior instrument adjusted to the Sharia context, then analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The measurement model results indicate that all constructs are valid and reliable (loading factor 0.60; AVE 0.50; composite reliability 0.70). Hypothesis testing results show that religiosity has a positive and significant effect on Islamic financial literacy (β = 0.54, p .001) and directly on family financial management behavior (β = 0.31, p .001), Islamic financial literacy has a positive and significant effect on family financial management behavior (β = 0.42, p .001), and Islamic financial literacy partially mediates the effect of religiosity on family financial management behavior (indirect effect β = 0.227, p .001), with a total effect of 0.537. These findings confirm that religiosity fosters healthier family financial behavior particularly when accompanied by adequate Islamic financial literacy, rather than through religious belief alone without sufficient financial knowledge.